Tuning the Anodic and Cathodic Dissolution of Gold by Varying the Surface Roughness - Chinnaiah, Jeyabharathi; Kasian, Olga; Dekshinamoorthy, Amuthan; Vijayaraghavan, Saranyan; Mayrhofer, Karl; Cherevko, Serhiy; Scholz, Fritz (ChemElectroChem, 2021)
This work presents the reactivity and dissolution of an as-polished and electrochemically pre-treated polycrystalline Au electrode, which is used as a model system. The effect of the electrochemical pre-treatment in corrosive 0.37 M HCl solutions on the Au surface roughness and dissolution is investigated by varying the number of pre-treatment steps at 1.16 V against the reversible hydrogen electrode. It is shown that the first 10 s pre-treatment of the as-polished Au results in a higher surface roughness and thus higher electrochemically active surface area (ECSA) than that of the as-polished Au. With the subsequent pre-treatments, however, the ECSA is gradually decreasing reaching a steady value. The dissolution rate of the pre-treated Au electrodes upon potential cycling in 0.1 M H2SO4 is determined by in situ inductively coupled plasma mass spectrometry. A non-linear dependence of Au dissolution amount is found with respect to the number of pre-treatments. The overall total Au dissolution rate follows a similar trend as ECSA/roughness. However, an important difference in the dissolution behavior is identified with respect to dissolution processes during Au oxidation (anodic dissolution) and Au reduction (cathodic dissolution): the former is more sensitive to the surface roughness. Thus, the ratio between Au anodic and cathodic dissolution amounts decreases substantially with decrease in surface roughness. This finding is explained by the slow and fast dissolution kinetics for anodic and cathodic processes, respectively. Current work further advances our understanding of the complex Au dissolution mechanism.
CRIS-Team Scopus Importer:2021-05-14
Keywords: corrosion; dissolution mechanism; gold dissolution; in situ-ICP-MS; surface state